Чалгиската музичка традиција во Македонија низ примерот на Велешката чалгија - Димитријевски, Александар (Асоциация за антропология, етнология и фолклористика »Онгъл«, 2018)
The Chalgija music tradition is one of the unique segments of the Macedonian music folklore. Mostly this is due to its origin and way of incorporation in the music culture, and on the other hand ‒ because of its intermingling musical influences from the broader and wider eastern and western cultures, but also because of the repertoire, which consists of diverse music examples. In this context, the Chalgija music in Macedonia is a representative of the urban music culture mostly from the period from the second half of the 19th and first half of the 20th century. It was wide spread in most of the cities in Macedonia, but the Chalgija music tradition from Veles, being one of the most representative and most known, was the dominant represent in the Macedonian Chalgija music tradition in general. In this paper, I will try to determine the place and the role of the Veles Chalgija music tradition, its most prolific representatives- performers, and its typical repertoire.
The Chalgija music tradition in Macedonia thru the example of the Chalgija from Veles
Issue No: 16, THE FIELDS OF ETHNOLOGY: BETWEEN KNOWLEDGE AND COGNITION. 25 YEARS ‘ONGAL’ ASSOCIATION
Keywords: Chalgija; Macedonian music folklore; Veles